Responsivitas Pelayanan Publik pada Pelayanan Pasien BPJS Rumah Sakit Umum Daerah Dr. R.M Djoelham Kota Binjai - Prasetyo, Edi; Nasution, Irwan; Angelia, Nina (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2024)
In general, this study aims to analyze the responsiveness of health services in RSUD Dr. R.M Djoelham, Binjai City. The problem is focused on one of the Regional General Hospital Dr. R.M Djoelham Binjai City in providing services for BPJS patients at RSUD Dr. R.M Djoelham has not been optimal. In order to approach this problem, it can be measured using Zeithaml's theory which consists of: the ability to respond, speed of service, accuracy of service, accuracy of service, timeliness of service. This research use desciptive qualitative approach. The data collection used was observation, interviews and documentation which was carried out for about one month. The results showed that in general the level of Responsiveness of BPJS Patient Public Services in the ability to respond, speed of service, accuracy of service, accuracy of service, timeliness of service was good, but in indicators of ability to respond to complaints there were several things that needed attention from the RSUD Dr. R.M Djoelham such as patient comfort and hospital facilities.